2011
DOI: 10.1038/ncb2385
|View full text |Cite
|
Sign up to set email alerts
|

The opposing transcriptional functions of Sin3a and c-Myc are required to maintain tissue homeostasis

Abstract: How the proto-oncogene c-Myc balances the processes of stem cell self-renewal, proliferation and differentiation in adult tissues is largely unknown. We explored c-Myc’s transcriptional roles at the Epidermal Differentiation Complex (EDC) a locus essential for skin maturation. Binding of c-Myc can simultaneously recruit (Klf4, Ovo1-1) and displace (C/EBPα, Mxi1 and Sin3A) specific sets of differentiation-specific transcriptional regulators to EDC genes. We found that Sin3A causes de-acetylation of c-Myc protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 59 publications
5
50
0
Order By: Relevance
“…HEK293T cells were transfected with expression vec- tors for Myc, Sin3b, and the acetyltransferase Kat2a (GCN5), and 24 h after transfection the levels of acetylated Myc were assessed by immunoblot with anti-acetyl-Lys in the immunoprecipitates obtained with anti-Myc. The results showed that Kat2a expression resulted in Myc acetylation, as reported previously (53), and that levels of acetylated Myc dramatically decreased upon the expression of Sin3b (Fig. 9A).…”
Section: Sin3b Identified As a Myc Interactor In A Yeast Two-hybridsupporting
confidence: 69%
See 1 more Smart Citation
“…HEK293T cells were transfected with expression vec- tors for Myc, Sin3b, and the acetyltransferase Kat2a (GCN5), and 24 h after transfection the levels of acetylated Myc were assessed by immunoblot with anti-acetyl-Lys in the immunoprecipitates obtained with anti-Myc. The results showed that Kat2a expression resulted in Myc acetylation, as reported previously (53), and that levels of acetylated Myc dramatically decreased upon the expression of Sin3b (Fig. 9A).…”
Section: Sin3b Identified As a Myc Interactor In A Yeast Two-hybridsupporting
confidence: 69%
“…Myc has been shown to be acetylated, which regulates Myc stability (49 -52). On the other hand, it has been reported that Sin3a induces deacetylation of Myc protein resulting in decreased Myc stability (53). We asked whether this was also the case with Sin3b.…”
Section: Sin3b Identified As a Myc Interactor In A Yeast Two-hybridmentioning
confidence: 96%
“…OVOL1 was specifically observed in the nuclei of cortex and outer root sheath cells, and OVOL2 was present in the nuclei of outer root sheath cells. It is known that OVOL1 is recruited to epidermal differentiation complex genes, leading to promoting keratinocyte differentiation, 11 and OVOL2 suppresses terminal differentiation of keratinocytes by directly repressing c-myc and Notch-1. The nuclear staining of OVOL1 and OVOL2 in ORS and germ (in addition to above mentioned facts) suggests that OVOL1 and OVOL2 are important transcriptional factors …”
Section: Discussionmentioning
confidence: 99%
“…Since SIN3A-mediated deacetylation of MYC has been demonstrated to trigger the degradation of this transcription factor (Nascimento et al 2011), it is likely that the dissociation of HDAC-containing complexes upon H3S28 phosphorylation constitutes a convenient mechanism to modulate transcription by inducing local changes in acetylation of chromatin-bound factors, thereby regulating their activity. Given that MSK1/2 were shown to phosphorylate other factors besides histone H3 (Wiggin et al 2002), we cannot exclude the possibility that such modifications, in addition to H3S28ph, play a role in transcriptional induction of stress-induced genes.…”
Section: Discussionmentioning
confidence: 99%